2003
DOI: 10.1074/jbc.m210129200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Protein-bound Endogenous Aldehydes

Abstract: 4-Hydroxy-2-nonenal (HNE), a major racemic product of lipid peroxidation, reacts with histidine to form a stable HNE-histidine Michael addition-type adduct possessing three chiral centers in the cyclic hemiacetal structure. In the present study, we characterized configurational isomers of a HNE-N ␣ -acetylhistidine adduct by NMR spectroscopy and by molecular orbital calculations. In addition, we raised monoclonal antibodies against (R)-HNE-histidine and (S)-HNE-histidine adducts, characterized their specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…In contrast to the nuclear staining with mAb21, the acrolein-lysine adduct immunoreactive with mAb5F6 was mainly detected in the cytoplasm. This pattern of distribution in the rat kidney was consistent with that of the distribution of other lipid peroxidation products and their conjugates with cytosolic proteins (15,23,24). In addition, these and the observation that the acrolein-derived adducts co-localized with 8-oxo-2Ј-deoxyguanosine, a marker of oxidative stress, strongly suggest that acrolein was generated under oxidative stress.…”
Section: Formation Of Acrolein-2ј-deoxyadenosine Adduct In the Renal supporting
confidence: 61%
“…In contrast to the nuclear staining with mAb21, the acrolein-lysine adduct immunoreactive with mAb5F6 was mainly detected in the cytoplasm. This pattern of distribution in the rat kidney was consistent with that of the distribution of other lipid peroxidation products and their conjugates with cytosolic proteins (15,23,24). In addition, these and the observation that the acrolein-derived adducts co-localized with 8-oxo-2Ј-deoxyguanosine, a marker of oxidative stress, strongly suggest that acrolein was generated under oxidative stress.…”
Section: Formation Of Acrolein-2ј-deoxyadenosine Adduct In the Renal supporting
confidence: 61%
“…We have previously described the preparation and characterization of the monoclonal antibody mAbR310 (Hashimoto et al, 2003) and its Fab fragment (Akagawa et al, 2006). The antibody was cleaved into its Fab and Fc fragments using an ImmunoPure Fab Preparation kit (Pierce).…”
Section: Crystallization and Data Collection Of Mabr310 Fab Fragmentmentioning
confidence: 99%
“…The novel monoclonal antibody mAbR310 against (R)-HNEmodified keyhole limpet haemocyanin showed the highest affinity for the (R)-HNE-treated protein and had a higher affinity for the mixture of 2R,4S,5R and 2S,4S,5R HNE-histidine adduct isomers than for HNE-lysine and HNE-cysteine adducts (Hashimoto et al, 2003). An immunohistochemical study using mAbR310 and anti-(S)-HNEmodified protein monoclonal antibody mAbS412 revealed that the (R)-and (S)-HNE epitopes are differentially distributed in the kidney of rats exposed to Fe 3+ -NTA (Hashimoto et al, 2003;Toyokuni et al, 1994). Very recently, the bispecific character of mAbR310 against modified protein and DNA and the structure of mAbR310 complexed with antigen were reported (Akagawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reaction with protein, HNE specifically reacts with nucleophilic amino acids, such as cysteine, histidine, and lysine, to form stable Michael addition adducts possessing three chiral centers at C-2, C-4, and C-5 in the cyclic hemiacetal structure (Fig. 1A) (5). Because of this chirality, the HNE adduct is composed of eight configurational isomers.…”
mentioning
confidence: 99%